Vitamin D, Race, and Excessive Daytime Sleepiness - McCarty, David E. (American Academy of Sleep Medicine, 2012)
STUDY OBJECTIVES: First, to determine whether serum vitamin D levels were correlated with excessive daytime sleepiness (EDS) in patients with or without vitamin D deficiency (VitDd). Second, to assess whether race affected the relation between vitamin D levels and EDS. METHODS: Serum 25-hydroxyvitamin D (25OHD) was measured by immunoassay in a consecutive series of 81 sleep clinic patients who complained of sleep problems and nonspecific pain (25OHD < 20 ng/mL ' VitDd). Sleepiness was determined using the Epworth Sleepiness Scale score ([ESSs] ESSs ≥ 10 ' EDS). Correlations were assessed using Pearson r. RESULTS: In patients without VitDd (25OHD ≥ 20 ng/mL), ESSs was inversely correlated with vitamin D concentration (r = 0.45, p < 0.05). The group consisted of 6% black patients, compared with 35% for the entire cohort. Among the patients who had VitDd (25OHD < 20 ng/mL), ESSs was directly correlated with 25OHD in black (r = 0.48, p < 0.05) but not white patients. In black patients, mean ESSs in patients with VitDd were higher and 25OHD levels were lower p < 0.05). CONCLUSIONS: The results suggested the novel possibility that VitDd-related disease has a yet-to-be-identified mechanistic role in the presentation of sleepiness, sleep disorders, or both. Further research is needed to clarify the mechanism(s) involved in producing the complex relationships noted. COMMENTARY: A commentary on this article appears in this issue on page 699. CITATION: McCarty DE; Reddy A; Keigley Q; Kim PY; Marino AA. Vitamin D, race, and excessive daytime sleepiness. J Clin Sleep Med 2012;8(6):693-697.